Identification of a functional vitamin D response element in the promoter of goose anti-Müllerian hormone gene - Rong Chen; Chen Chen; Yifei Qin; Jie Liu; Mingming Lei; Huanxi Zhu; Zhendan Shi (Poultry Science)
Anti-Müllerian hormone (AMH) plays an important role in avian ovarian follicle development. The high mRNA expression of AMH in avian ovarian prehierarchical follicles helps prevent premature granulosa cell differentiation. Vitamin D3 was reported to downregulate AMH mRNA expression in granulosa cells of prehierarchical follicles in hens; however, the underlying molecular mechanism remains unknown. In this study, AMH mRNA expression was investigated in granulosa cells of prehierarchical follicles in geese under vitamin D3 induction. A potential vitamin D response element (VDRE) present in the goose AMH promoter was identified using luciferase activity, electrophoretic mobility shift assay (EMSA), and chromatin immunoprecipitation (ChIP) assays. The results showed that AMH mRNA expressions were downregulated by vitamin D3 in granulosa cells of prehierarchical follicles in geese. A classical VDRE-like sequence was identified in the goose AMH promoter by in silico analyses. Luciferase activity assays revealed that the putative VDRE is a negative regulatory element. Vitamin D receptor (VDR) and retinoic X receptor (RXR) are necessary to decrease the AMH promoter activity induced by vitamin D3. The EMSA and ChIP assays demonstrated that the VDR/RXR complex directly binds to the putative VDRE. These results suggest that vitamin D3 downregulates AMH mRNA expression via a functional VDRE that binds the VDR/RXR heterodimer in goose ovarian prehierarchical follicles. These results provide new insights into the regulatory mechanisms of vitamin D3 in avian ovarian follicular development.